Soil organic carbon and nutrient contents are not influenced by exclosures established in communal grazing land in Nile Basin, northern Ethiopia - Mekuria, Wolde; Langan, Simon J.; Noble, A.D.; Johnston, Robyn M. (International Institute of Engineers, 2014)
Land degradation through extensification of agriculture and overgrazing is an increasing problem across large expanses of the Ethiopian highlands that give rise to a loss in a range of ecosystem services. Ecological restoration through exclosure establishment has become increasingly important approach to reversing degraded ecosystems in Ethiopia and particularly in the Amhara regional state, northern Ethiopia. The present study was conducted in Nile basin, northern Ethiopia to investigate the changes in soil properties and nutrient contents following establishing exclosures on communal grazing lands. A space-for-time substitution approach to monitor changes in soil properties after conversion of communal grazing lands to exclosures with ages of establishment ranging from 1 to 7-years was used. In the 0- to 20- and 20- to 50-cm depths, significant (p < 0.05) differences in soil pH, exchangeable cations, cation exchange capacity, soil moisture content, and bulk density were observed among exclosures and between exclosures and communal grazing land. Communal grazing land displayed significantly higher soil total nitrogen, phosphorus and potassium compared to exclosures. However, differences between exclosures and grazing land in soil organic matter (SOM) content and soil organic carbon (SOC) stock were not significant (p > 0.05). The results demonstrated that exclosure age influenced SOM content and SOC stock. The lack of influence in soil nutrient and SOM contents as well as SOC stock after 7-year of exclosure establishment could be attributed to: (a) the favorable environment (e.g., better moisture content and soil pH) in exclosures, which results in increased SOM decomposition, and (b) better vegetation growth in exclosures, which consequently reduce soil nutrient content due to higher nutrient uptake by restored plants. Exclosures alone therefore cannot be regarded as a comprehensive short- or medium-term soil rehabilitation option.